Behavioural Study of Captive Sloth Bears Using Environmental Enrichment Tools - M. Veeraselvam; R. Sridhar; M. G. Jayathangaraj; P. Perumal (International Journal of Zoology)
Effects of environmental enrichment on behavioural changes were studied in five captive sloth bears kept in confined enclosure at Zoological Park, Chennai, India. Behavioural categories like active, passive, and abnormal behaviours were taken for the study. The activity budget was recorded as a single animal scan. The detailed baseline data of 150 hours, over a period of 30 days, were collected. At baseline, bears exhibited passive and more abnormal behaviours. Similarly, after application of the environmental tools like honey-log, underground food pipes, and wobbling box in the enclosure, the data were collected for 150 hours (30 days). Increased active behaviours and decreased abnormal behaviours were observed and showed highly significant changes in the abnormal behaviour as a whole when compared to the baseline level. During the postenrichment period, the data that were collected for 150 hours (30 days) showed no significant differences statistically between the behavioural categories. But certain level of difference was evident from the percentage of abnormal behaviours exhibited by individual bears. Among the enrichment devices, honey-log was the most preferred enrichment tool as revealed by the percentage of time spent by individual animal. The results show that application of enrichment tool continuously may bring long term effect in stereotypic behaviour.